2021
DOI: 10.1186/s12891-021-04638-2
|View full text |Cite
|
Sign up to set email alerts
|

Modified F configuration in the treatment of Pauwels type III femoral neck fracture: a finite element analysis

Abstract: Background The optimal treatment of Pauwels type III femoral neck fracture (FNF) in young patients remains a worldwide challenge in orthopedic surgery. Methods Finite element models of four internal fixations were developed to treat Pauwels type III FNF: a: the traditional inverted triangular parallel cannulated screw (PCS) model, b: the F-technique cannulated screw model, c: the modified F-technique cannulated screw model using a fully threaded sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The rationale for this phenomenon might be attributed to the augmented cross‐sectional area and the structurally robust triangular arrangement of multiple screws, which possess the capability to distribute stress from the upper part of the femoral head to the calcar, making it more conducive for weight bearing 15,28 . Nevertheless, similar to our investigation, previous finite element analyses had suggested that CCS exhibited inadequate mechanical stability in withstanding high shear and inversion forces at fracture sites, potentially leading to varus deformity, nonunion, femoral neck shortening and femoral head necrosis after surgery 17,29 . Likewise, Liporace et al 4 .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The rationale for this phenomenon might be attributed to the augmented cross‐sectional area and the structurally robust triangular arrangement of multiple screws, which possess the capability to distribute stress from the upper part of the femoral head to the calcar, making it more conducive for weight bearing 15,28 . Nevertheless, similar to our investigation, previous finite element analyses had suggested that CCS exhibited inadequate mechanical stability in withstanding high shear and inversion forces at fracture sites, potentially leading to varus deformity, nonunion, femoral neck shortening and femoral head necrosis after surgery 17,29 . Likewise, Liporace et al 4 .…”
Section: Discussionsupporting
confidence: 69%
“…15,28 Nevertheless, similar to our investigation, previous finite element analyses had suggested that CCS exhibited inadequate mechanical stability in withstanding high shear and inversion forces at fracture sites, potentially leading to varus deformity, nonunion, femoral neck shortening and femoral head necrosis after surgery. 17,29 Likewise, Liporace et al 4 showed that the overall rate of postoperative complications was 32% in the fixation of Pauwels type III fractures using an "inverted triangle" CCS, with a non-union rate of 19% and an incidence of femoral head necrosis rate of 14%. Consequently, based on our findings, we did not advocate for the use of CCS in the fixation of Pauwels type III fractures.…”
Section: Ccsmentioning
confidence: 99%
“…[ 45 ]. Nevertheless, the estimated load (2–3 times body weight or 2100 ​N) used for the load input in the FEA method in the previous computational studies [ 2 , 5 , 20 , 46 ], which was lower than the result calculated by the musculoskeletal multibody dynamics model based on the subject's experimental data. Therefore, considering the higher hip joint force employed as the load input in the FEA method in the present study, the maximum stresses/displacements in the hybrid/conventional cannulated screw system were higher than those in the previous computational studies [ 2 , 5 , 12 ].…”
Section: Discussionmentioning
confidence: 89%
“…FCS aims to increase the stability of internal fixation while retaining the minimally invasive advantages of TCS. Lin et al ( 19 ) reported that in finite element analysis, a modified F-technique configuration (similar to our FCS technique) showed a better performance in resisting shearing and rotational forces in treating Pauwels type III femoral neck fracture compared to those using traditional inverted triangular TCS. However, few studies have compared the clinical results of FCS with TCS.…”
Section: Discussionmentioning
confidence: 92%